Argument Evaluation Test for Critical Thinking Ability Assessment: A Preliminary Study - Christin N. K. Lunggito; Anindito Aditomo; Ide Bagus Siaputra (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Critical thinking is a highly valued learning outcome in all educational levels. This study explores students ability to evaluate arguments as one manifestation of critical thinking. Using a newly developed instument (the Argument Evaluation Test), we describe high school graduates’ (N = 2201) ability to distinguish between sound and fallacious arguments, without explicit instruction. The results indicate that about half of the participants were able to spontaneously evaluate arguments and identify logical fallacies. This is significant considering that argumentation and logical fallacies are not part of the school curriculum in Indonesia. Thus, the ability to identify at least some types of logical fallacies could be obtained through informal learning and therefore the knowledge underlying this ability is likely to be implicit. Another finding was that the ability to evaluate arguments seem to vary depending on the type of fallacy, with ad hominem arguments easier to be identified as fallacious compared to ad populum arguments, as well as demographic variables such as gender and ethnicity.